PREPARASI PEREAKSI KIT IMMUNORADIOMETRlCASSAY FREE PROSTATE SPECIFIC ANTIGEN UNTUK DETEKSI KANKER PROSTAT - Puji Widayati; Gina Mondrida; Sri Setiyowati; Agus Ariyanto; V. Yulianti Susilo; Wening Lestari (Jurnal Kimia Terapan Indonesia, 2013)
Prostate Specific Antigen (PSA) is a glycoprotein with a molecular weight of approximately 34,000 daltons serine protease secreted exclusively by prostatic epithelial cells that lining acini and prostate gland. Increased of PSA levels can be caused by prostate cancer or benign prostate enlargement (benign prostatic hyperplasia, BPH). PSA in the blood was found in the free condition (free PSA) and most of the bound protein (complexed-PSA, c-PSA). Measuring levels of PSA was found in the blood can be done by several methods such as by immunoradiometricassay (IRMA) methods or ELISA methods. IRMA method is one of immunoassay techniques using radionuclides ,/' 125 oJ I as a tracer, so the sample in small 13 quantity can be detected The purpose of this study was obtained PSA reagent kit that includes 1251labeled PSA as a tracer, PSA coated tube and PSA standard that requirements of the kit, then it can be optimized assay design, that eventually PSA reagent kit can be used for early detection of prostate cancer. It has been done labeling of Mab PSA using 125 1with reaction time was 90 seconds, amount of PSA MAb was 75 ugram and the activity of Na_ 125I was 1000 flCi. Preaparation of PSA coated tube using 0.05 M Na2C03 solution, at pH: 9.6 with volume was 250 ml., standard PSA with 0.025 Mphosphate buffer at pH 7.4 containing 5% BSA and 0.1% NaN3, and resulting at 1,25% and 14,12% respectively of NSB and BIT that requirement of the kit.Keywords: Prostate cancer, PSA, IRMA,NSB, Maximum Binding